Distribution Network Optimization Based on Genetic Algorithm - Syahputra, Ramadoni (Journal of Electrical Technology UMY, 2017)
This paper presents a new robust optimization technique for distribution network configuration, which can be regarded as a modification of the recently developed genetic algorithm. The multi-objective genetic algorithm has been applied to this problem to optimize the total cost while simultaneously minimize the power loss and maximize the voltage profile. The IEEE 69-bus distribution network is used in the tests, and test results have shown that the algorithm can determine the set of optimal nondominated solutions. It allows the utility to obtain the optimal configuration of the network to achieve the best system with the lowest cost.